2022
DOI: 10.1158/2767-9764.crc-22-0157
|View full text |Cite
|
Sign up to set email alerts
|

A Miniaturized Screening Platform to Identify Novel Regulators of Extracellular Matrix Alignment

Abstract: Extracellular matrix alignment contributes to metastasis in a number of cancers and is a known prognostic stromal factor; however, the mechanisms controlling matrix organization remain unclear. Cancer-associated fibroblasts (CAF) play a critical role in this process, particularly via matrix production and modulation of key signaling pathways controlling cell adhesion and contractility. Stroma normalization, as opposed to elimination, is a highly sought strategy, and screening for drugs that effectively alter e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 114 publications
0
6
0
Order By: Relevance
“…It was reported that p53 was regulated through the TrkA and p75 neurotrophin receptors in neonatal sympathetic neurons ( Aloyz et al, 1998 ). As for ECM organization in the previous study, the researchers developed a high-throughput screening platform using fibroblast-derived matrices imaged with automated confocal microscopy in 384-well plates to explore mechanisms controlling matrix organization ( Jones et al, 2022 ). It was identified that NTRK1 was one of the modulators of matrix alignment.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that p53 was regulated through the TrkA and p75 neurotrophin receptors in neonatal sympathetic neurons ( Aloyz et al, 1998 ). As for ECM organization in the previous study, the researchers developed a high-throughput screening platform using fibroblast-derived matrices imaged with automated confocal microscopy in 384-well plates to explore mechanisms controlling matrix organization ( Jones et al, 2022 ). It was identified that NTRK1 was one of the modulators of matrix alignment.…”
Section: Discussionmentioning
confidence: 99%
“…The top-enriched term is the vitamin D receptor pathway, which ameliorates breast cancer by contributing to the growth regulation of breast cancer cells [54,55]. Other enriched terms, such as NABA MATRISOME ASSOCIATED, mammary gland development, and extracellular matrix organization, have been reported to play a key role in various biological processes related to breast cancer progression and treatment [56][57][58][59][60]. In Supplementary Enirchment_Dataset1, we list Metascape enrichment analysis results related to Dataset1.…”
Section: Dataset1mentioning
confidence: 99%
“…We had 11 treatments in which the 736 samples were distributed accodingly as follows. Paclitaxel (169), Paclitaxel + ABT 888 + Carboplatin (63) (49). The gene expression data was performed using Reverse Phase Protein Array (RPPA) microarray at George Mason University.…”
Section: Gse196093: Dataset3mentioning
confidence: 99%